Profitability Mediates the Effect of Managerial Ownership, Company Size, and Leverage on the Disclosure of Intellectual Capital - Barokah, Lefi; Fachrurrozie, Fachrurrozie (Accounting Analysis Journal, 2019)
The aims of this research are to examine the effect of managerial ownership, firm size and leverage on intellectual capital disclosure by accommodated profitability as mediating variable that mediated the effect of firm size and leverage. The population in this study was34 banking companies listed in Indonesian Stock Exchange (BEI) in 2014-2017. The sample selection used purposive sampling method and collected 38 samples with152 unit analysis. The hypotheses testing used path analysis by IBM SPSS AMOS version 22. The results of analysis showed that firm size has a positive significant effect on intellectual capital disclosure and profitability. Leverage has a negative significant effect on intellectual capital disclosure. The results showed that the level of intellectual capital disclosure banking sector in Indonesia is quite high 50,52%. Profitability failed to mediate firm size and leverage on intellectual capital disclosure. The further research can use other types of intellectual capital intensive industry sectors such as electrical, information technology and services. The management of the companies are expected to be able to manage the assets resources well. Use the nominal value of intellectual capital owned by the company to measure intellectual capital disclosure.